Dependência espacial e convergência local da renda entre os municípios do Nordeste: 2000-2010 - Cruz, Italo Spinelli da (2013)
Brazil s northeast, notably known because of its intraregional inequalities in its income and welfare, presented a process of considerable growth in its added product in the last decade. Although some improvements regarding that region s income growth can be verified, it is questioned if these improvements were enough to mitigate the inequalities found among Brazil s northeast cities in the recent decade. The process of income convergence in that region has been the object of empirical and econometric studies since the end of 1990s. However, some of these works do not take into account either spatial standard of cities growth or the spatial interactions that can occur among them. In this sense, this work aims at analysing the process of income convergence from the work in the northeast s cities between 2000 and 2010, taking into consideration the effects of the existing spatial interactions among cities in the aforementioned region. Moreover, it is used techniques from Exploratory Spatial Data Analysis (ESDA) and the models developed by the Spatial Econometrics as well as Geographically Weighted Regressions (GWR). Lall and Shalizi (2003) analysed the influence of spatial effects in the process of income convergence among northeast s cities in a previous period, and this is why their work is taken as an analytical reference. Initially, it is updated and incorporated in the modellings of those theorists as an alternative treatment to the spatial differentiation. It is analysed the process of local convergence concerning each northeast s town, which allows the discussion of the existing heterogeneity in that region. The results indicate a very slow process of convergence among northeast s cities. Nevertheless, it is possible to verify processes of convergence in which cities spatially associated present a process of a more intense convergence, while other groups of cities present a pattern of low convergence in the period.